Síndrome de Lynch: Abordagem Clínica - Campos, Sara (2010)
About 2-3% of colorectal cancer occurs in the context of Lynch syndrome, which is due to germline mutations in one allele of mismatch repair genes. Lynch syndrome is also associated with a high risk of extracolonic cancers, including gynecological, gastric, small bowel, biliopancreatic tract, urinary tract, skin and central nervous system. In this review we discuss cancer risks, early diagnosis methods in the context of Lynch syndrome and provide recommendations for clinical management concerning affected families. Considering other types than extracolonic cancer, evidence supporting surveillance is scarce. A benefit of surveillance is evident only for colorectal cancer and endometrial cancer, in which colonoscopy and transvaginal ultrasound plus endometrial sampling detect tumours in early stages. Surveillance is also recommended for urinary tract and gastric cancer. On what concerns the remaining cancers, surveillance is typically not recommended. For individual who will undergo surgical resection for colon cancer, total colectomy is favored. Prophylactic hysterectomy and bilateral salpingo-oophorectomy should be considered for women with Lynch syndrome who are past childbearing age, especially during surgery for colorectal cancer.